Experimental Research on High Temperature Resistance of Modified Lightweight Concrete after Exposure to Elevated Temperatures - Ke-cheng He; Rong-xin Guo; Qian-min Ma; Feng Yan; Zhi-wei Lin; Yan-Lin Sun (Advances in Materials Science and Engineering)
In order to improve the spalling resistance of lightweight aggregate concrete at high temperature, two types of modified materials were used to modify clay ceramsite lightweight aggregates by adopting the surface coating modification method. Spalling of the concrete specimens manufactured by using the modified aggregates was observed during a temperature elevation. Mass loss and residual axial compressive strength of the modified concrete specimens after exposure to elevated temperatures were also tested. Concrete specimens consisting of ordinary clay ceramsites and crushed limestone were manufactured as references for comparison. The results showed that the ordinary lightweight concrete specimens and the crushed limestone concrete specimens were completely spalled after exposure to target temperatures above 400°C and 1000°C, respectively, whereas the modified concrete specimens remained intact at 1200°C, at which approximately 25% to 38% of the residual compressive strength was retained. The results indicated that the modified lightweight concrete specimens have exhibited superior mechanical properties and resistance to thermal spalling after exposure to elevated temperatures.